Analysis of intention toward halal products: an empirical study of young consumers - Budi Harsanto; Dika Jatnika (Universitas Hayam Wuruk Perbanas, 2017)
The purpose of this paper is to determine the intention of consumer in choosing halal products, particularly for food products. The three main elements in the Theory of Planned Behavior (TPB) consisting of attitude, subjective norm, and perceived behavioral control is connected to the intention to consume halal products, particularly halal food. This study refers to the two studies both in the Malaysian context. This is a survey-based research. It used a questionnaire for collecting the data taken from Â 151 active students of Faculty of Economics and Business in Unpad who participated as the respondents in this research. The data were analysed using a descriptive statistics, correlation, chi-square. and multiple regression. The findings show that the three main elements have a significance effect on the intention. This study is unique since it was conducted in Indonesiaâ€™s context and the results is slightly different from the findings of the previous one.